Loss of organic matter and nutrients аt soil water erosion on slope lands - Tsybulka, Mikalai M.; Zhukova, Inna I.; Yukhnovets, Aksana V. (Journal of the Belarusian State University. Ecology, 2022)
The results of long-term studies of the flushing of humus and plant nutrition elements with water erosion on sod-podzolic soils are presented. Quantitative indicators of their losses with liquid and solid runoff during spring snowmelt and precipitation of runoff-forming rains under different agricultural crops have been established.During the spring snowmelt, the maximum runoff was observed on winter grain crops, the maximum soil washout was observed on winter plowing. Humus, nitrogen, phosphorus and potassium are lost mainly with solid runoff. During the spring snowmelt, the total losses of humus, nitrogen, phosphorus and potassium are 80.4, 5.4, 2.3 and 2.1 kg/ha per year, respectively, on winter crops - 28.6, 1.7, 0.7 and 0.6 kg/ha per year, under perennial grasses - 5.3, 0.2, 0.2 and 0.9 kg/ha per year.The maximum runoff and flushing of the soil during the fallout of runoff-forming rains was observed under row crops, the minimum - under perennial grasses. The main losses of humus, nitrogen and phosphorus under row and spring grain crops are noted with solid runoff. Under perennial grasses, humus is washed off more with liquid, and nitrogen and phosphorus -in equal amounts with liquid and solid runoff. Potassium is mainly carried out with the soil on row crops, and on winter cereals - with liquid runoff. On spring grain crops and perennial grasses, its losses with liquid and solid runoff are the same.In general, when cultivating row crops, humus losses with water erosion reach 240 kg/ ha per year, under spring grain and leguminous crops - 8-170, under winter grain - 25-45 kg / ha per year, and under perennial grasses no more than 10 kg/ha. Total nitrogen losses range from 12.5-46.0 kg/ha under row crops to 1.5-5.0 kg/ha under winter grain crops. Phosphorus and potassium losses amount to 4.5-20.0 kg/ha per year on row crops, 3.5-15.0 - on spring cereals and leguminous crops, 1.5-7.0 - on winter cereals and less than 2 kg/ha per year on perennial grasses.
Keywords: water erosion; liquid runoff; soil runoff; losses; humus; nitrogen; phosphorus; potassium